2012
DOI: 10.1016/j.joep.2012.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Savings adequacy uncertainty: Driver or obstacle to increased pension contributions?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 48 publications
(72 reference statements)
0
14
0
Order By: Relevance
“…SII was adapted from Bearden et al (). Perceived financial uncertainty was measured by a question inspired by van Schie, Donkers, and Dellaert (). Perceived helpfulness was adapted from the measure by Chen and Wells ().…”
Section: Methodsmentioning
confidence: 99%
“…SII was adapted from Bearden et al (). Perceived financial uncertainty was measured by a question inspired by van Schie, Donkers, and Dellaert (). Perceived helpfulness was adapted from the measure by Chen and Wells ().…”
Section: Methodsmentioning
confidence: 99%
“…Existing strategies of nancing childbirth Income has often been cited as the most robust predictor of overall nancing savings (30). However, studies conducted to test this hypothesis are inconclusive as some authors have found that populations with lower incomes may also engage in savings (31). There is a scarcity of evidence suggesting that the hyperin ationary economy in Zimbabwe has lowered the nancing of maternal savings (32).…”
Section: Discussionmentioning
confidence: 99%
“…21 Researchers and policymakers have used this panel to study a broad variety of topics, including pension-related issues (e.g. Alessie et al 2011, Van Duijn et al 2013and Van Schie et al 2012). An important feature of this panel is that a wide range of information on the panellists can be found in the DNB Household Survey (DHS) database.…”
Section: Our 2015 Survey On Pension Pattern Preferences and Their Drimentioning
confidence: 99%